ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CORPORATE SUSTAINABILITY PERFORMANCE - Puspita, Anitya Ardiyani; Daljono, Daljono (Diponegoro Journal of Accounting, 2014)
This study aim to analyze the determinant of Corporate Sustainability Performance in Indonesia. Factors tested in this study are firm size, leverage, profitability, growth option, firm commitment, public ownership and firm age. The population in this study consist of all listed firms in Indonesia Stock Exchange in year 2008-2012. Sampling method used is purposive sampling. A criterion for Corporate Sustainability Performance is a company which is including in SRI KEHATI Index. Data used in this study are company including in SRI KEHATI Index and non SRI KEHATI Index, the sample consist of 250 companies. Logistic regression used to be analysis technique.The empirical result of this study show that firm size, profitability, growth option, public ownership have positively significant influence on probability of Corporate Sustainability Performance, besides leverage has negatively significant. Firm commitment and firm age have no significant influence to probability of Corporate Sustainability Performance.